2016
DOI: 10.1063/1.4964286
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the problem of uniform converging spherical shock wave in water

Abstract: Time-resolved parameters of plasma compressed by a shock wave generated by the underwater electrical explosion of a spherical wire array are presented. The plasma was preliminarily formed inside a capillary placed at the equatorial plane along the axis of the array. Temporal evolution analysis of Hα and C II spectral lines showed that the plasma density increases from its initial value of ∼3 × 1017 cm−3 up to ∼5.5 × 1017 cm−3 within 300 ± 25 ns. These results were found to be in agreement with those of the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…So far our experimental attempts for the observation of sonoluminescence in our specific cylindrical configuration and liquid confinement of bubble implosion has been unsuccessful. At the moment, the present work of converging shock-driven bubble creation and implosion opens novel perspectives and challenges in the frame of high amplitude shock waves in liquids and energetic cavitation [17,18,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…So far our experimental attempts for the observation of sonoluminescence in our specific cylindrical configuration and liquid confinement of bubble implosion has been unsuccessful. At the moment, the present work of converging shock-driven bubble creation and implosion opens novel perspectives and challenges in the frame of high amplitude shock waves in liquids and energetic cavitation [17,18,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Based on twodimensional (2D) hydrodynamic simulations, Kozlov et al compared the effect of shock front instability with different wavelengths on the energy cumulation process and the pressure in the vicinity of implosion axis, pointing out corrugation effect and convergence effect jointly determine the growth of perturbations [6]. Nitishinskiy et al estimated the pressure behind the incident converging shock front near the implosion origin of spherical wire array using the time-resolved optical emission spectrum of capillary plasma, and the result agreed well with 1D hydrodynamic model, which indirectly proved the uniformity of the converging shock waves [7]. Yanuka et al observed the uniformity of cylindrical converging shock waves at a very small radius using laser backlit framing images.…”
Section: Introductionmentioning
confidence: 88%